2022
DOI: 10.1002/trc2.12326
|View full text |Cite
|
Sign up to set email alerts
|

Differences and similarities between familial and sporadic frontotemporal dementia: An Italian single‐center cohort study

Abstract: Introduction The possibility to generalize our understandings on treatments and assessments to both familial frontotemporal dementia (f‐FTD) and sporadic FTD (s‐FTD) is a fundamental perspective for the near future, considering the constant advancement in potential disease‐modifying therapies that target particular genetic forms of FTD. We aimed to investigate differences in clinical features, cerebrospinal fluid (CSF), and blood‐based biomarkers between f‐FTD and s‐FTD. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 63 publications
(110 reference statements)
0
2
0
Order By: Relevance
“…Increased CSF NfL, in both genetic and sporadic subtypes, has been associated with various progression measures, including CDR, cognition (executive functioning; neuropsychiatry unit cognitive assessment tool), behavioral symptoms (FBI), frontotemporal GM atrophy, WM tract pathophysiology, GABA-ergic deficit, and survival rates ( Scherling et al, 2014 ; Kassubek et al, 2018 ; Steinacker et al, 2018 ; Benussi et al, 2020 ; Spotorno et al, 2020 ; Walia et al, 2022 ). Interestingly, when comparing genetic and sporadic subtypes, a large cross-sectional study concluded that serum NfL concentration is higher in genetic bvFTD ( Benussi et al, 2022 ). Another promising, less validated fluid biomarker is soluble triggering receptor expressed on myeloid cells 2 (sTREM2).…”
Section: Resultsmentioning
confidence: 99%
“…Increased CSF NfL, in both genetic and sporadic subtypes, has been associated with various progression measures, including CDR, cognition (executive functioning; neuropsychiatry unit cognitive assessment tool), behavioral symptoms (FBI), frontotemporal GM atrophy, WM tract pathophysiology, GABA-ergic deficit, and survival rates ( Scherling et al, 2014 ; Kassubek et al, 2018 ; Steinacker et al, 2018 ; Benussi et al, 2020 ; Spotorno et al, 2020 ; Walia et al, 2022 ). Interestingly, when comparing genetic and sporadic subtypes, a large cross-sectional study concluded that serum NfL concentration is higher in genetic bvFTD ( Benussi et al, 2022 ). Another promising, less validated fluid biomarker is soluble triggering receptor expressed on myeloid cells 2 (sTREM2).…”
Section: Resultsmentioning
confidence: 99%
“…Although classified as rare diseases, they are each caused by a well-defined mutation in a single protein. Monogenic neurodegenerative diseases, including genetic forms of Alzheimer's disease 9,10 , Parkinson's disease, and prion diseases have become popular in scientific research as their study offers several advantages 11 : While differences in clinical symptoms and pathological changes exist between genetic and sporadic forms of the same disease, there is also considerable overlap [12][13][14] , suggesting findings may translate between different disease forms. Furthermore, they are easier to replicate in a disease model than sporadic or polygenic diseases, which have a more complex etiology involving interactions of genetic and environmental factors.…”
Section: Introductionmentioning
confidence: 99%